(untitled) (Window of Public Health Journal, 2025)
Work-life balance is a state of equilibrium between work and life, where a person is equally committed to both work responsibilities and family or personal life responsibilities. Work-life balance is an important factor for every nurse, ensuring that nurses maintain a balanced quality in their relationships with their families and achieve a balance in their work. This study aims to determine factors related to work-life balance in married female nurses in the inpatient ward of the Dadi Regional Special Hospital (RSKD) in South Sulawesi Province. This study used a quantitative research method with an observational analytical design and a cross-sectional study approach. The sampling technique used in this study employed a total sampling approach, where all members of the population were included, specifically 68 nurses. Data analysis employed both univariate and bivariate analyses, utilizing the chi-square test. This research instrument used a questionnaire. According to the results of the chi-square test, there is a relationship between workload and work life balance, namely (p = 0.000 <0.05), there is a relationship between length of service and work life balance, namely (p = 0.028 <0.05), there is a relationship between family support and work life balance, namely (p = 0.000 <0.05), and there is no relationship between welfare and work life balance, namely (p = 0.078>0.05) in married female nurses in the inpatient room of Dadi Regional Special Hospital, South Sulawesi Province. This study concludes that there is a relationship between workload, length of service, and family support, and work-life balance, but no relationship between welfare and work-life balance, among married female nurses in the inpatient room of Dadi Regional Special Hospital (RSKD), South Sulawesi Province.